Mile 81 [compact disc, unabridged] - King, Stephen, 1947- (Audioworks, 2012)
Young Pete Simmons just wanted to have some fun and explore when he stumbled onto the old abandoned rest stop at Mile 81 on the Maine turnpike. Instead, he discovers a scene of bloodshed and carnage. A car has pulled into the boarded-up service station, a run-down, muddy station wagon without any plates, and without a driver. As the car claims the lives of one would-be good Samaritan after another, Pete decides that it's up to him to stop the evil car before he becomes its next victim.